Taxonomy of dinoflagellates, the genus Protoperidium (Archaeperidinium), in coastal waters of Vietnam - Luom, Phan Tan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2016)
Species of the subgenus Archaeperidinium belonging to genus Protoperidinium were characterized by its morphology, such as “ortho”-type of the first apical plate and two intercalary plates. A total of tenArchaeperidinium species have been found in coastal  waters of Vietnam, in which, six species, viz.P. abei var. rotundata,P.compressum, P. stellatum.P. cf. planiceps, P. latum and P. nux were newly recorded for the Dinoflagellate flora in coastalwaters of Vietnam. All the six species have been described and illustrated in shape, size and the ornamentation of the theca under light microscopy.